Gendered Regret in Chinese University English Classrooms: Toward a Five-Dimensional Analytical Framework - Hou, Jing; Tian, Xiaoming; Sun, Siyi (Journal of Education and Learning Environments, 2026)
This study uses semi-structured interviews to examine the emergence of gendered regrets in Chinese university English classrooms. Reflexive thematic analysis of interviews with 36 teachers and 53 students across 23 universities identifies how pedagogical practices, student psychology, social expectations, pragmatic language use, and intercultural communication interact to shape gendered experiences. Drawing on these findings, the study introduces the 'Regret Pentagon Diagram', a conceptual framework that categorizes the five dimensions contributing to gendered regret. Pedagogical practices, such as gendered grouping or role expectations, can limit student participation and agency. Psychological factors reveal how students experience self-doubt, discomfort, or exclusion when gendered assumptions conflict with individual identity. Social expectations, including teachers' authority and perceived social status, influence students’ gendered sense of fairness and opportunity. Pragmatic issues highlight how language choices and framing may unintentionally reinforce gender stereotypes, while intercultural communication demonstrates how culturally informed gender expectations can create tension in cross-cultural classrooms. The analysis shows that teachers' unexamined gender assumptions and insufficient cultural sensitivity can lead to student alienation, disengagement, and emotional distress. The study underscores the importance of gender-sensitive pedagogy, reflective teaching practice, and intercultural competence to promote equitable, inclusive, and context-responsive learning environments.